Building Joyful Learning to Enhance Students Motivation in Studying English - Permana, Rian Sigit Gesang; Roni, May; Rahmawati, Widya; H, Ari Fatihatul; Susanto, Susanto (CV. Creative Tugu Pena, 2022)
Learning is enhanced when it accours within a positive condition where the students fell exitement about what they are learning. Students are the center of learning process. They are forced to be active in reading, doing tasks, and in answering teacher’s question. The article aimed to discuss the characteristics of joyful learning, students’ motivation and the influence of joyful learning in building students’ motivation in studying English. The researchers used library research. For this reason, the researchers have proven it through analytical efforts and in-depth studies in several international publications. In short, the researchers examined each piece of evidence with a phenomenological approach to get answers to research questions that are among other things, involve a data coding system, critical evaluation, and drawing of valid and reliable final results . The result show that teachers can identify the characteristic of their students, so they can choose the kind of the appropriate educative games they can give. So although they come from different background, the students still have a high motivation in studying English. Teacher is demanded to be able to implement a concept that can create a fun learning situation in the class, so that the students feel comfortable and happy during teaching and learning process Keywords: Building Joyful Learning, Students Motivation, Joyful Learning English